PEMANFAATAN MULTIPLY UNTUK PEMASARAN PRODUK IKM DI YOGYAKARTA - Hernikawati, Dewi (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2010)
Multiply is one of the biogs that used by entrepreneurs to market their products. The method used in this research is a case study with a qualitative approach. Data were collected by conducting in-depth observation and interviews with informants (small and medium industry) in Yogyakarta. Multiply has advantages compared with mass media for cost and efficiency. Multiply used for business facilities are still very limited, only for young entrepreneurs who are creative and innovative with the Internet.